Pendidikan Islam Kasik: Telaah Rasulullah SAW Sebagai Pendidik Ideal - Seswi Derti; Zulmuqim Zulmuqim; Fauza Masyhudi (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Pre-Islamic Arabia is known to be far from civilized and even far from humane. Warfare between tribes occurs everywhere due to power struggles and so on. It is not surprising that this period is usually called the period of ignorance. This article formulates the history of classical Islamic education regarding Pre-Islamic Arabia and the profile of the Prophet as an ideal educator. This research is library research, namely looking for data related to research in the form of the Koran, books and journals. which aims to find out Islamic Education in the classical period. For this reason, this article will reveal the picture of pre-Islamic Arabia and the profile of the Prophet Muhammad as an ideal educator in Islamic education.